Sistem Informasi Jadwal Dan Pemesanan Tiket Keberangkatan Kapal Laut Di Pelabuhan Jangkar Berbasis Android - M Syafiih; Nur Istifadah; Nur Hatima Inda Arifin (Department of Science and Technology Ibrahimy University, 2022)
The port is a place consisting of land and waters around it with certain as a place of economic activity and activities, the surrounding area becomes a place to lean, up and down passengers or unloading goods equipped with shipping safety facilities. Anchors Port which was built in 1986 to serve loading and unloading of passenger goods for alternative crossings connected between the island of Java and many islands and regencies in Madura, especially Kalianget and Sumenep districts (Sapudi, Raas and Kangean Islands), Anchors Harbor is located in Asembagus District, 35 km east of Situbondo, East Java Province. Ship transportation crossings at Anchors Situbondo port, sometimes not fixed with an uncertain departure schedule, departure schedules and ticket reservations are still made manually, namely from the bookkeeping and have not been equipped with information system devices to manage ship schedules. So from these problems, an android-based application was created that can be used as an android-based schedule information system and ticket booking for ship departures with the aim of making it easier for prospective passengers to find out departure schedules and ticket reservations. The method used is the waterfall method with flowchart, DFD and ERD tools so that the management of information systems is more systematic. The results of this test are to produce an android-based schedule information system application and ship departure ticket booking which shows a percentage of 90.6% with the category strongly agreeing to be used.